Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4040/jkan.2009.39.5.683
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Symptom Clusters in Patients with Hepatocellular Carcinoma

Abstract: Purpose:The purpose of this study was to identify cancer-related symptom clusters and to validate the conceptual meanings of the revealed symptom clusters in patients with hepatocellular carcinoma. Methods: This study was a cross-sectional survey and methodological study. Patients with hepatocellular carcinoma (N=194) were recruited from a medical center in Seoul. The 20-item Symptom Checklist was used to assess patients' symptom severity. Selected symptoms were factored using principal-axis factoring with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Our study also found that patients experienced highest levels of fatigue and depression at T5 (5 days after treating TACE initiation) in both groups. The level of fatigue was moderate; this finding was similar to previous studies [ 4 , 11 , 12 ], in which most cancer patients suffered from fatigue during and after treatment. The time point of peak fatigue and depression was at treatment completion and preparation for hospital discharge, and these distressing problems may impact physical function and daily living.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also found that patients experienced highest levels of fatigue and depression at T5 (5 days after treating TACE initiation) in both groups. The level of fatigue was moderate; this finding was similar to previous studies [ 4 , 11 , 12 ], in which most cancer patients suffered from fatigue during and after treatment. The time point of peak fatigue and depression was at treatment completion and preparation for hospital discharge, and these distressing problems may impact physical function and daily living.…”
Section: Discussionsupporting
confidence: 91%
“…Research also verified that Taiwanese patients with HCC receiving TACE experienced moderate levels of fatigue which peaked at 2 days after initial TACE [ 9 ]. In several studies [ 4 – 6 , 10 ] of HCC patients receiving TACE, it was reported that fatigue was the most common adverse effect causing sleep disturbances [ 5 ], reduced physical and emotional status [ 11 ], and produced a negative effect on overall quality of life [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… Symptoms and symptom clusters impact on QoL: Patients with lower symptoms had significantly higher QoL scores than those with higher symptoms. 7 1, 2, 5 Cho et al., 2009 [ 17 ] Korea To explore cancer-related symptom clusters. Observational study with cross-sectional survey - factor analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies focused on symptom prevalence and symptom severity primarily occurring in HCC patients [ 8 , 9 , 11 , [16] , [17] , [18] , [19] , [20] , 23 , 25 ]. Three studies focused on the specific symptoms which occurred, including sleep disturbance [ 24 ], fatigue, depression [ 22 , 24 ], and pain [ 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation